Gendering climate change: a feminist criminological perspective - Wonders, Nancy A. (Critical criminology, 2015)
Drawing on insights from feminist scholars and activists, this article examines the dialectical relationship between climate change and the social construction of gender. We examine in detail how gender inequalities associated with capitalism, particularly in its latest Neoliberal incarnation, help to produce global warming, as well as to produce gendered vulnerabilities and unequal impacts. After a brief review of past successes and failures to integrate gender concerns into climate change debates and policies, we suggest several criminological interventions that are compatible with a feminist perspective on climate change. We argue that a stronger criminological focus on the global political economy, particularly on the gendered inequalities it produces, is analytically essential for understanding both the etiology and harmful consequences of climate change. Simultaneously, we urge critical criminologists to employ the tools of our trade to take a more proactive role in the social construction of a just and sustainable society.